The turn of the dice: Patrick Hughes' Hollow Dice and Reverspectives. (March 2023) - Rogers, Brian; Hughes, Patrick
Patrick Hughes' Reverspectives demonstrate the importance of perspective as a source of information about the structure and layout of the three-dimensional (3D) world. More recently, he has created a new work of art— Hollow Dice— in which the actual concave structure of the dice is seen as convex . In this article, we examine the similarities and differences between these two perceptual phenomena as well as attempting to explain how and why they arise. Popular interest in both effects is based on the fact that " what we perceive " does not correspond to " what the reality is ." As a consequence, Reverspectives and Hollow Dice are often categorized and labeled as "illusions." However, if we consider the information that is available in patterns of light reaching our eyes—rather than the "actual" 3D structure of the Reverspectives and the Hollow Dice— we are in a better position to explain how the size, the viewing distance, the perspective features, the convexity bias, and observer movements determine what we see when viewing these novel and fascinating visual effects.